Effect of Nasya Karma in the Management of Avabahuka - A Case Study - Nupur Biswas (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is the traditional medical science of India. Vata aggravated brings about contractions of the Siras (nerves) of the Arm and produce the disease Avabahuka (Frozen Shoulder) then occurs Pain & loss of movement of the arm. Avabahuka is a disease that causes problems in daily activities of an individual like dressing, eating, personal hygiene and work. Shoulder joint is the most mobile joint in the body. Clinical presentation and pathogenesis of Avabahuka It Can be correlated with Frozen Shoulder. In classics, Nasya is indicated for Avabahuka. The aim of the present study was to evaluate the effectiveness of Nasya karma on Avabahuka. Method: In our Panchakarma OPD 55 years old male patient came with chronic pain in both shoulders joint. Patient was unable to movement both hand & he was Unable to carry out daily activities. Patient was taken 15 days Panchakarma therapy, After Snehana Nadi Swedana Nasya karma was done by Anu Tailam. Result: After 15 days of treatment there was marked relief of the symptoms like Pain, Stiffness etc. Conclusion: The therapies were found significantly effective and clinically safe and no adverse reactions were reported during the treatment period.